Framing the doctor-patient relationship in chronic illness: a comparative study of general practitioners' accounts. - May, C; Allison, G; Chapple, A; Chew-Graham, C; Dixon, C; Gask, L; Graham, R; Rogers, A; Roland, M (2004)
How family doctors conceptualise chronic illness in the consultation has important implications for both the delivery of medical care, and its experience by patients. In this paper, we present the results of a re-analysis of qualitative data collected in a series of studies of British family doctors between 1995 and 2001, to explore the ways in which the legitimacy and authority of medical knowledge and practice are organised and worked out in relation to three kinds of chronic illness (menorrhagia; depression; and chronic low back pain/medically unexplained symptoms). We present a comparative analysis of (a). the moral evaluation of the patient (and judgements about the legitimacy of symptom presentation); (b). the possibilities of disposal; and (c). doctors' empathic responses to the patient, in each of these clinical cases. Our analysis defines some of the fundamental conditions through which general practitioners frame their relationships with patients presenting complex but sometimes diffuse combinations of 'social', 'psychological' and 'medical' symptoms. These are fundamental to, yet barely touched by, the increasingly voluminous literature on how doctors should interact with patients. Moving beyond the individual studies from which our data are drawn, we have outlined some of the highly complex and demanding features of what is often seen as routine and unrewarding medical work, and some of the key requirements for the local negotiation of patients' problems and their meanings (for both patients and doctors) in everyday general practice.